BETWEEN UNCERTAINTY AND AUTONOMY: PERCEPTIONS OF THE NURSING TEAM IN THE IMPLEMENTATION OF ROBOTIC SURGERY (REMUNOM, 2026)
Introduction: Robotic surgery is one of the main technological innovations in contemporary surgical practice, integrating high-precision computerized systems that enhance the surgeon’s dexterity, provide magnified three-dimensional vision, and enable safer and more stable movements, resulting in reduced tissue trauma and faster patient recovery. Its incorporation across different specialties has required the reorganization of work processes, specific training, and adaptation of nursing teams to new technological demands in the perioperative context. Objective: To understand the perceptions of the nursing team regarding the implementation of robotic surgery in a private hospital in Joinville, Santa Catarina, Brazil. Method: This is a qualitative study conducted through interviews with nursing professionals working in robotic surgery within a surgical center. Results: The introduction of robotic technology was initially associated with feelings of uncertainty and apprehension, especially related to handling the equipment due to its complexity and high technological value. With training and supervised practice, these feelings were replaced by confidence, technical competence, and familiarity with the system. Participants highlighted benefits such as greater surgical precision, faster patient recovery, reduced errors, and improved organization of teamwork. Professional training was identified as a key factor for successful implementation, emphasizing the importance of continuing education and institutional support. Conclusion: Robotic surgery represents a significant advancement for perioperative nursing, promoting technical qualification, professional recognition, and improved patient safety, despite the initial challenges of adaptation.